Analisis Pengaruh Kualitas Pelayanan, Kualitas Produk Dan Citra Merek Terhadap Kepuasan Pelanggan Dan Dampaknya Pada Loyalitas Pelanggan Waroeng Spesial Sambal - Parman, Parman; Susanto, Susanto (Universitas Muhammadiyah Yogyakarta, 2016)
Companies in the future will increasingly depend on the brand, which means it is not enough to just-oriented services and products. To continue to improve its business and face competition Waroeng